Socioformative Educational Model for Sustainable Social Development in Higher Education (Docentes 2.0 Journal, 2025)
Higher education institutions face the challenge of educating well-rounded individuals capable of addressing social problems while contributing to sustainable social development. The objective was to analyze the characteristics of the socio-formative educational model as a proposal for change that seeks to respond to the challenges of Latin American society. A research project was conducted within the framework of the socio-constructivist paradigm, using an interpretive method, a qualitative approach, a thematic narrative design, a bibliographic documentary, and a cross-sectional analysis. This research involved collecting and reviewing various texts published from 2013 to 2024 from the databases Scopus, Web of Science, Scielo, Redalyc, Dialnet, and Google Scholar. Thematic analysis was applied to these documents, which made it possible to establish three categories: contributions, characteristics, and aspects to consider in implementing the socio-formative educational model. The results indicate that this educational model focuses on solving contextual problems by implementing projects that promote collaboration and the ethical development of individuals. It also highlights the importance of incorporating technologies into co-creating knowledge and formative assessment of the performance of students and the institutions themselves. In conclusion, the socio-formative educational model represents an alternative for change in the transformation of higher education institutions. Still, its success depends on institutional leadership capable of promoting collaborative work and the formative development of the university community.
Keywords: Sustainable social development; higher education; integral formation; educational model; socioformation